Chalcone-Derived Dihydropyrazoles as Dual Antiproliferative and Antioxidant Agents: Insights from Synthesis, Assays and EGFR Docking - Haque, K M Ferdousul; Hossain, Md Khalid; Al Mansur, Muhammad Abdullah; Rashid, Mohammad A; Rahman, Mohammad Sharifur (Bangladesh Pharmaceutical Journal, 2026)
Chalcones are conjugated 1,3-unsaturated ketones that have a variety of pharmacological properties, such as antidiabetic, antioxidant and anticancer actions. Current study showed that, a chalcone, (E)-1,3-diphenylprop-2-en-1-one (1) was synthesized by reacting benzaldehyde with acetophenone. This compound was subsequently added with hydrazine hydrate and hydrazine hydrate in the attendance of acetic acid to yield two pyrazole derivatives, namely 3,5-diphenyl-4,5-dihydro-1H-pyrazole (2) and 1-(3,5-diphenyl-4,5-dihydropyrazol-1-yl) ethanone (3). The synthesized compounds were characterized using FTIR and 1H NMR spectroscopy. Compounds 1 to 3 demonstrated significant cytotoxic activity against the HeLa cell line. Additionally, they exhibited notable antioxidant properties. In silico studies were performed to evaluate the drug-likeness, pharmacokinetic profiles and molecular docking interconnections with the epidermal growth factor receptor (EGFR). These computational analyses provided insights into the potentiality of the compounds for drug-receptor binding and their pharmacokinetic behaviors. This work reports, for the first time, the comparative biological and computational studies conducted here. However, further detailed investigations are required to fully understand their mechanisms of action. Bangladesh Pharmaceutical Journal 29(1): 27-39, 2026 (January)